2022
DOI: 10.1007/s11356-022-19992-4
|View full text |Cite
|
Sign up to set email alerts
|

Does health expenditure matter for life expectancy in Mediterranean countries?

Abstract: This research assesses the effect of health expenditure and sanitation on life expectancy in Mediterranean countries. We also consider other drivers of life expectancy, such as CO 2 emissions and economic growth. The study covers the period 2000–2018, and the recently developed method of moments quantile regression (MMQR) approach was utilised to assess these interconnections. This method is immune to outliers and creates an asymmetric interrelationship between variables. The outcomes fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 90 publications
1
11
0
Order By: Relevance
“…A possible explanation for this finding is that the various health authorities in Africa are judiciously using the funds allocated to the health sector in the provision of healthcare services and related activities aimed at improving the lives of individuals in the respective countries. The significant positive impact of total health expenditure on average life expectancy is consistent with previous studies (Bein et al, 2017;Shahraki, 2019;Behera and Dash, 2020;Nkemgha et al, 2021;Radmehr and Adebayo, 2022).…”
Section: Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…A possible explanation for this finding is that the various health authorities in Africa are judiciously using the funds allocated to the health sector in the provision of healthcare services and related activities aimed at improving the lives of individuals in the respective countries. The significant positive impact of total health expenditure on average life expectancy is consistent with previous studies (Bein et al, 2017;Shahraki, 2019;Behera and Dash, 2020;Nkemgha et al, 2021;Radmehr and Adebayo, 2022).…”
Section: Discussion Of Resultssupporting
confidence: 92%
“…Applying the robust least squares regression technique, the findings indicated that general government health expenditure (in terms of out-of-pocket payment and external health expenditure) positively and significantly drives life expectancy. Radmehr and Adebayo (2022) analyzed the impact of health expenditure and sanitation on life expectancy in Mediterranean countries. Employing the method of moments quantile regression technique, the authors established that health expenditure improves life expectancy in the sampled countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To address the first study objective, the study adapts the econometric construct of prior studies (Adeleye et al, 2022;Adeleye, Tiwari, et al, 2023;Azam et al, 2023;Barua et al, 2022;Das & Debanth, 2023;Radmehr & Adebayo, 2022) to express life expectancy as a function of each emissions source and a set of control variables. For empirical analysis, Equation ( 2) is specified explicitly as:…”
Section: Theoretical Framework and Model Constructmentioning
confidence: 99%
“…Table 1 provides a summary of these studies. The literature in Table 1 might be classified as follows: i) There is a consensus in the literature that environmental degradation rises infant mortality (Ecevit & Çetin, 2016;Majeed & Khan, 2019;Erdoğan et al, 2019;Shobande, 2020;Majeed & Ozturk, 2020;Omri et al, 2022;Yu et al, 2022;Tsai et al, 2022;Barua et al, 2022) and reduces life expectancy (Balan, 2016;Sirag et al, 2017;Matthew et al, 2018;Nkalu & Edeme, 2019;Erdoğan et al, 2019;Majeed & Khan, 2019;Majeed & Ozturk, 2020;Akter et al, 2020;Hossain et al, 2020;Rodriguez-Alvarez, 2021;Murthy et al, 2021;Alimi & Ajide, 2021;Chen et al, 2021;Bouchoucha, 2021;Rjoub et al, 2021;Azam et al, 2022;Omri et al, 2022;Rahman & Alam, 2022a;Arafat et al, 2022;Radmehr & Adebayo, 2022;Salehnia et al, 2022;Ibrahim, 2022;Bayar et al, 2022). Also, Mutizwa and Makochekanwa (2015) concluded that environmental degradation does not have an impact on infant mortality.…”
Section: Literaturementioning
confidence: 99%